(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This paper reviews the regulatory overlaps and conflicts in the regulation of engineering professions in Kenya. It is based on the recognition that the engineering profession is very instrumental to national development. The review finds out that the overlaps have led to regulatory inconsistency and duplicity, and legal wrangles. To cure these anomalies the paper recommends the development of a regulatory policy framework based on the paradigm of whole- of-government approach and the concept of regulatory quality.